Acidovorax citrulli Type III Effector AopP Suppresses Plant Immunity by Targeting the Watermelon Transcription Factor WRKY6 - Zhang, Xiaoxiao; Yang, Yuwen; Zhao, Mei; Yang, Linlin; Jiang, Jie; Walcott, Ron; Yang, Shanshan; Zhao, Tingchang (Frontiers in Plant Science, 2020)
Acidovorax citrulli (Ac) is the causal agent of bacterial fruit blotch and a global threat to watermelon and melon production. Despite its economic importance, little is known about the molecular mechanisms underlying Ac pathogenicity and virulence, particularly with regard to its type III secreted effectors. Here, we identified a new effector AopP in Ac and confirmed its secretion and translocation. AopP suppressed reactive oxygen species burst and salicylic acid content and significantly contributed to virulence by interacting with a watermelon transcription factor, ClWRKY6, in vivo and in vitro. Subcellular localization showed that ClWRKY6 had a typical nuclear localization feature. Moreover, AopP and ClWRKY6 were found to co-localize in the nucleus. Importantly, the expression of ClWRKY6 was induced by salicylic acid at the transcriptional and translational levels in watermelon. Furthermore, Ac infection and the pathogen-associated molecular pattern flg22Ac prompted ClWRKY6 production, indicating that ClWRKY6 was involved in plant immunity. In summary, we identified a novel effector as a virulence mechanism of Ac, which interacts with the transcription factor of the natural host watermelon. These results provide insights into the mechanisms of watermelon immune responses and may facilitate molecular breeding for bacterial fruit botch resistance.